For your own good - Horlick, Leah (Caitlin Press, 2015)
In the canon of contemporary feminist and lesbian poetry, For Your Own Good breaks silence. A fictionalized autobiography, the poems in this collection illustrate the narrator's survival of a domestic and sexual violence in a lesbian relationship. There is magic in this work: the symbolism of the Tarot and the roots of Jewish heritage, but also the magic that is at the heart of transformation and survival. These poems are acutely painful, rooted in singular and firsthand experiences. But Horlick also draws from a legacy of feminist, Jewish and lesbian writers against violence: epigraphs from the works of Adrienne Rich and Minnie Bruce Pratt act as touchstones alongside references to contemporary writers, such as Daphne Gottlieb and Michelle Tea. In this reflection on grief, silence and community, we follow the narrator's own journey as she explores what it is to survive, to change, to desire and to hope. At once unflinching and fragile For Your Own Good is a collection with transformation at its heart.
Keywords: amériques; autobiographie; canada; genre; personnes lesbiennes; poésie; régions géographiques; thématiques; violences; violences conjugales